Deoxyribo Nucleic Acid (DNA) in the Alquran Perspective - Utari, Nahyulia Liza; Marini, Elis; Rahman, Achyar; Buchari, Buchari; Zulkarim, Zulkarim (International Journal of Multidisciplinary Research of Higher Education, 2024)
Biological facts have been mentioned in the Alquran, which was revealed over 1400 years ago and is proven correct by scientists today. This study focuses on implicit and explicit interpretations of human creation, biological development, and genetic concepts. By using a multidisciplinary approach that combines the maudhu'i method of interpretation, scientific and genetic approaches, as well as textual, intertextual, and contextual interpretation techniques. This study found a connection between Deoxyribo Nucleic Acid (DNA) and the Alquran that is implied in the concept of “nutfah”. The analysis shows that the Alquran mentions various fluids involved in the fertilization process, including sperm, poured fluid, hated fluid, and mixed fluid. This research emphasizes the role of Deoxyribo Nucleic Acid (DNA) as the “master key” that controls human physical and mental functions, and its interaction with the environment in activating certain genes. Deoxyribo Nucleic Acid (DNA) is understood as the “blueprint of life” that stores biological information and plays an important role in the transmission of hereditary traits.